2018
DOI: 10.3390/atmos9070238
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and Mineralogical Effects on Ice Nucleation Activity of Volcanic Ash

Abstract: Volcanic ash produced during explosive eruptions may serve as ice nuclei in the atmosphere, contributing to the occurrence of volcanic lightning due to tribocharging from ice-ice or ice-ash collisions. Here, different ash samples were tested using deposition-mode and immersion-mode ice nucleation experiments. Results show that bulk composition and mineral abundance have no measurable effect on depositional freezing at the temperatures tested, as all samples have similar ice saturation ratios. In the immersion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 66 publications
0
16
1
Order By: Relevance
“…The mechanisms leading to ice nucleation by fine ash are complex and not well understood [64][65][66][67][68]. Mineral composition appears also to be an important factor [69,70].…”
Section: Volcanic Icementioning
confidence: 99%
“…The mechanisms leading to ice nucleation by fine ash are complex and not well understood [64][65][66][67][68]. Mineral composition appears also to be an important factor [69,70].…”
Section: Volcanic Icementioning
confidence: 99%
“…VA can act as INP depending on temperature and relative humidity conditions of the atmosphere. Previous studies on the ice nucleation properties of VA particles obtained from different sources under both mixed‐phase and cirrus cloud conditions have reported broadly different results (Durant et al., 2008; Fornea et al., 2009; Genareau et al., 2018; Gibbs et al., 2015; Hoyle et al., 2011; Jahn et al., 2019; Kulkarni et al., 2015; Mangan et al., 2017; Maters et al., 2019; Schill et al., 2015; Steinke et al., 2011). These studies have clearly established that VA particles can nucleate ice in the immersion freezing mode.…”
Section: Introductionmentioning
confidence: 95%
“…For example, Genareau et al. (2018) studied five VA samples and found that the most ice active VA sample had a high K 2 O and a low MnO content. Mangan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Similar factors might influence ice nucleation by volcanic ash (Kulkarni et al, 2015;Schill et al, 2015;Genareau et al, 2018).…”
mentioning
confidence: 99%